Persepsi Kemudahan Dan Persepsi Kegunaan Terhadap Kepatuhan Wajib Pajak Dimediasi Oleh Penggunaan E-Filing - Eva Stevanny Abuur; Maylen K. P Kambuaya; Hesty Theresia Salle (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
This study aims to test the Effect of Perceived Ease, Perception of Usefulness on Taxpayer Compliance in submitting Annual Tax Returns with the Use of E-Filing as an Intervening Variable. This research uses a quantitative approach. Data collection was carried out using the Purposive Sampling technique. The data used are primary data obtained by distributing questionnaires. The subjects in this study are taxpayers who have an TIN. The sample used in this study was 100 respondents. The data analysis technique uses Non Probalility Sampling which is a technique that does not provide the same opportunity for each element or member of the population to be selected to be sampled with the help of using the SMARTPLS version 3.0 program. The results of this study are The Perception of Ease has a positive and significant effect on the Taxpayer's Propriety, the Perception of Usefulness has a positive and significant effect on The Compliance of The Mandatory The use of e-filing has a positive and significant impact on Taxpayer Compliance, the Perception of Ease has a positive and significant effect on Taxpayer Compliance through the Use of E-Filing and the Perception of Usefulness has a positive and significant effect on Taxpayer Compliance through the Use of E-Filing.